Risk factors and outcomes of thyroid immune-related adverse events following PD-1/PD-L1 inhibitors treatment in a large tertiary Chinese center - Wenwen Gong; Erhan Zheng; Minchao Liu; Yaliang Han; Zhaohui Lyu; Qinghua Guo (BMC Endocrine Disorders)
Abstract Objective To investigate the clinical characteristics, related risk factors and outcomes of thyroid immune-related adverse events (irAEs) in patients with malignant solid tumor treated with programmed cell death-1 (PD-1) or programmed cell death-ligand 1 (PD-L1) inhibitors in a large tertiary Chinese center. Methods We retrospectively analyzed the clinical data of 1151 patients with malignant solid tumors who received PD-1 or PD-L1 inhibitors treatment and underwent thyroid function evaluation in a large 3 A hospital of Beijing from September 2019 to December 2023. According to the thyroid status after receiving PD-1/PD-L1 inhibitors treatment, patients were divided into normal thyroid group and thyroid irAEs group. The clinical characteristics, including age, gender, tumor type, previous anti-cancer treatment history and thyroid function status were evaluated. After the occurrence of thyroid irAEs, thyroid function evaluation, onset time, and survival outcomes were analyzed. Risk factors that may contribute to the thyroid irAEs were further explored by logistic regression. Results Out of 1151 patients treated with a PD-1/PD-L1 inhibitor, 257 (22.3%) developed new thyroid irAEs, with the vast majority (98.0%) being hypothyroidism (193/257, 75.1%) and Grade1-2 (252/257, 98.0%), including 252 Hashimoto’s thyroiditis (98.0%), 3 subacute thyroiditis (1.17%) and 2 Graves’ disease (0.78%). There was a significant difference in the number of treatment cycles of PD-1/PD-L1 inhibitors between the two groups (P = 0.001). In multivariate analysis, gastrointestinal cancer, radiotherapy history, targeted therapy history, positive TgAb and TPOAb at baseline were associated with thyroid irAEs caused by PD-1/PD-L1 inhibitors. Absence of thyroid irAEs predicted increased mortality overall (HR = 2.935, P = 0.024) and particularly in gastrointestinal cancers (HR = 9.453, P = 0.007), despite comparable crude mortality (5.84% vs. 5.82%, P = 0.228). No association was observed in lung/other tumors. Thyroid function recovery occurred in 36.2% of patients, and treatment interruption due to thyroid irAEs was rare (3.5%). Conclusion In our group, 22.3% patients treated with PD-1/PD-L1 inhibitors developed thyroid irAEs. The main subtype of thyroid irAEs was hypothyroidism (75.1%). Patients with gastrointestinal cancer, previous radiotherapy, history of targeted therapy, and baseline TgAb or TPOAb positivity may increase the risk of thyroid irAEs. Thyroid irAEs was associated with a trend for a survival benefit in patients with gastrointestinal cancer.